1991
DOI: 10.1017/s0890037x00028189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Safener CGA-154281 on Metolachlor/Atrazine Injury to Corn (Zea mays)

Abstract: Three seed lots each of two varieties of field corn were compared in greenhouse and field studies. Cold test germination percentages of the seed lots were as follows: 79, 85, and 93% for ‘DK656’; 77, 84, and 91% for ‘T1100’. Tank mixes of metolachlor or metolachlor with safener CGA-154281 plus atrazine or formulated metolachlor/atrazine with and without the safener were applied preemergence. Crop stand of either variety or among seed lots within a variety was not affected by herbicide treatments. In the greenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…611 may be tolerant to metolachlor or the GDD were sufficient to over come delay in maturity. Others have shown that metolachlor at X -and 2X-rate did not significantly reduce com yields on soils where seedbeds were prepared with tillage even though there was visual herbicide injury earlier (14,21). The shortage of sufficient GDD at North Platte and Sidney hindered grain development but not stover development (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…611 may be tolerant to metolachlor or the GDD were sufficient to over come delay in maturity. Others have shown that metolachlor at X -and 2X-rate did not significantly reduce com yields on soils where seedbeds were prepared with tillage even though there was visual herbicide injury earlier (14,21). The shortage of sufficient GDD at North Platte and Sidney hindered grain development but not stover development (Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…Com during early July did not exhibit typical chloroacetamide injury symptoms such as twisting and curling of leaves and shoot height reductions (9,14). This might have been due to metolachlor being intercepted by the crop residue and less be ing available to cause early com injury symptoms (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbicide safeners have been used to reduce crop injury and expand the window of application for several herbicides. For example, metolachlor applied preplant or PRE in corn can cause crop injury under cool, wet soil conditions (Foy and Witt 1991). The addition of the safener benoxacor [4-(dichloroacetyl)-3,4-dihydro-3-methyl-2H-1,4-benzoxazine] to metolachlor reduced corn injury caused by metolachlor under unfavorable soil conditions (Foy and Witt 1991;Viger et al 1991).…”
mentioning
confidence: 99%
“…For example, metolachlor applied preplant or PRE in corn can cause crop injury under cool, wet soil conditions (Foy and Witt 1991). The addition of the safener benoxacor [4-(dichloroacetyl)-3,4-dihydro-3-methyl-2H-1,4-benzoxazine] to metolachlor reduced corn injury caused by metolachlor under unfavorable soil conditions (Foy and Witt 1991;Viger et al 1991). The addition of the safener cyprosulfamide {N-[[4-[(cyclopropylamino)carbonyl]phenyl]sulfonyl]-2-methoxybenzamide} to isoxaflutole extended the use pattern of this herbicide in corn from PRE to POST use up to the two-leaf collar stage of corn growth (Nelson and Penner 2006;Philbrook and Santel 2008).…”
mentioning
confidence: 99%